Effective Encoding for DNA Sequence Visualization Based on Nucleotide's Ring Structure - A.T.M. Golam Bari; Rokeya Reaz; A.K.M. Tauhidul Islam; Ho-Jin Choi; Byeong-Soo Jeong (Evolutionary Bioinformatics, 2013)
Effective representation of DNA sequences is one of the important tasks in the study of genome sequences. In this paper, we propose a graphical representation of DNA sequences based on nucleotide ring structure. In the proposed representation, we convert DNA sequences into 16 dinucleotides on the surface of the hexagon so that it can preserve nucleotide's chemical property and positional information. Our approach can provide capability of efficient similarity comparison between DNA sequences and also high comparison accuracy. Furthermore, our approach satisfies uniqueness and no degeneracy of DNA sequences. In the experimental study, we use phylogeny analysis for evolutionary relationship among different species. Extensive performance study shows that the proposed method can give better performance than existing methods in comparison with the degree of similarity.